Broad host range phage vB-LmoM-SH3-3 reduces the risk of Listeria contamination in two types of ready-to-eat food. (February 2020) - Zhou, Chenlu; Zhu, Mengya; Wang, Yongjuan; Yang, Zhenquan; Ye, Mao; Wu, Litin; Bao, Hongduo; Pang, Maoda; Zhou, Yan; Wang, Ran; Sun, Lichang; Wang, Heye; et al.
Abstract: Listeria monocytogenes is a food borne pathogen causing listeriosis in humans and animals. L. monocytogenes can tolerate severe environments and food processing conditions by forming biofilms and becoming resistant to disinfectants. Thus, it is important to develop new strategies to control the contamination of L. monocytogenes and keep food safety. In the present study, a new L. monocytogenes phage vB-LmoM-SH3-3 (designated as phage SH3-3) was isolated from a food processing plant. The genome of phage SH3-3 shares homology with multiple non- Listeria phages, but shares low similarity with classical Listeria phages. Phage SH3-3 showed widely lytic activity to Listeria spp. including L. monocytogenes, L. innocua and L. welshimeri. With an efficient minimal inhibitory concentration, phage SH3-3 could also inhibit the formation of the dense and net-like structure of the L. monocytogenes biofilm. Moreover, phage SH3-3 showed high efficacy against L. monocytogenes in salmon meat and orange juice. Therefore, phage SH3-3 could be potentially used as a natural biocontrol preservative to reduce L. monocytogenes contamination in ready-to-eat food and during the processing stages of food production. Highlights: We isolated a broad host range phage SH3-3 that can lyse L. monocytogenes, L. innocua and L. welshimeri The genome of phage SH3-3 shares homology with non- Listeria phages, but shares low similarity with classical Listeria phages Phage SH3-3 can effectively inhibit biofilm formation and reduce contamination of L. monocytogenes in RTE food.